SOCIAL AND ECONOMIC PROBLEMS OF ORGANIZATION OF STATIONARY COGNITIVE TOURS (ON THE EXAMPLE OF LVIV) (INNOVATIVE ECONOMY, 2019)
Nykyha O.V. SOCIAL AND ECONOMIC PROBLEMS OF ORGANIZATION OF STATIONARY COGNITIVE TOURS (ON THE EXAMPLE OF LVIV)Purpose. The aim of the article is identifying and analysis of social and economic problems of organization of stationary educational tours in the big city on the example of Lviv.Methodology of research. The theoretical basis of the research is the scientific works on the economic, social and organizational aspects of the development of the tourist sphere of Ukraine. The following methods are used to achieve this goal: the method of analysis of scientific literature – to study approaches to understanding the nature and structure of cognitive tourism, features of the organization of cognitive tours; questionnaire method via the Internet (spontaneous sampling) – to get information about problems of organization of stationary educational tours in Lviv.Findings. The following social and economic problems of organization of inpatient educational tours in Lviv are highlighted, such as: lack of comfortable living conditions at an affordable price; restoration of historical sites; undifferentiated cognitive programs; aging of the tourist product; low development of the transport network, including communal public transport; poor quality of roads; no inland tourism advertising; unstable quality of excursions; false opinion about Lviv as a tourist-dangerous city.Originality. The research of problems of functioning of tourist destinations has been further developed. In particular, the list of problems of organization of stationary educational tours in the big city is formulated.Practical value. The results of the study can be used in the activity of tourism enterprises of Ukraine and Lviv, state authorities and local self-government. Theoretical and methodological generalizations may form the basis for further scientific research.Key words: cognitive tourism; destination; big city; stationary tour; excursion.
Keywords: Key words; cognitive tourism; destination; big city; stationary tour; excursion.